To assess knowledge, attitude and practice of lifestyle diseases and their risk factors among women in the urban field practice area - Bhavana, Mungara Suma; Kumar, Sunil D.; Chandan, N.; Lokesh, Derangula; Narayanamurthy, M. R. (International Journal Of Community Medicine And Public Health, 2021)
Background: The number of people suffering from lifestyle diseases is increasing over the world, causing significant morbidity and mortality, particularly in developing countries. Changes in behaviour and the adoption of healthy lifestyle practises can help prevent or reduce the progression of lifestyle diseases. Many patients, however, lacked the knowledge, attitude, and practise of healthy lifestyles. Methods: A cross-sectional study was conducted among the 329 participants in the urban field practice area of the department of community medicine, JSS medical college, Mysore, with study duration of 6 months. A house-to-house survey was performed to recruit study participants using convenient sampling. participants will be interviewed by using the pre-designed, pre-tested and structured questionnaire which includes socio-demographic profile, dietary patterns, physical activity, type of personality, history of stress, history of tobacco and alcohol consumption, family history of lifestyle diseases like HT, DM etc. Results: Among 329 study participants 306 (93%) have practice of doing physical exercise, 328 (99.7%) decreased salt/oil intake, 329 (100%) stopped smoking/alcohol consumption, 329 (100%) check BP regular, 327 (99.4%) check blood sugar regularly, 328 (99.7%) stopped eating junk food/cool drinks, 329 (100%) take medications Conclusions: Healthy practices need to be subsidized with the aid of using the dependent periodic medical exam. There need to be an emphasis on incorporating bodily workout within side the day by day routine, consumption of healthful diet, and decrease/cessation of alcohol and tobacco consumption.